Disharmony between wake- and respiration-promoting activities: effects of modafinil on ventilatory control in rodents. Issue 1 (December 2016) - Terada, Jiro; Fukushi, Isato; Takeda, Kotaro; Hasebe, Yohei; Pokorski, Mieczyslaw; Tatsumi, Koichiro; Okada, Yasumasa
Abstract Background Modafinil is a wake-promoting drug and has been widely used for daytime sleepiness in patients with narcolepsy and other sleep disorders. A recent case series reported that daily oral modafinil alleviated hypercapnic respiratory failure in patients with COPD. However, the precise action of modafinil on respiration such as hypercapnic and/or hypoxic ventilatory responses remains unclear. The aim of this study is to clarify the effect of modafinil on the ventilatory control. Methods We investigated the hypothesis that modafinil enhances resting ventilation as well as the stimulatory ventilatory responses to hypercapnia and hypoxia. We addressed the issue by examining minute ventilation, respiratory rate and volume components using plethysmography, combined with a concurrent EEG monitoring of the level of wakefulness before and after administration of modafinil in two doses of 100 mg/kg and 200 mg/kg in unanesthetized mice. In addition, we monitored the effect of the lower dose of modafinil on mice locomotor activity in a freely moving condition by video-recording. Results Wakefulness, locomotor activity and variability of the breathing pattern in tidal volume were promoted by both doses of modafinil. Neither dose of modafinil increased the absolute values of resting ventilation or promoted the ventilatory responses to hypercapnia and hypoxia. Rather, higher dose of modafinil slightly suppressed respiratory rate in room air condition. Conclusions Modafinil is conducive to the state of wakefulness but does not augment resting ventilation or the hyperventilatory responses to chemical stimuli in unanesthetized rodents.